2016
DOI: 10.1111/ejn.13243
|View full text |Cite
|
Sign up to set email alerts
|

Lack of mGluR6‐related cascade elements leads to retrograde trans‐synaptic effects on rod photoreceptor synapses via matrix‐associated proteins

Abstract: Heterotrimeric G-proteins couple metabotropic receptors to downstream effectors. In retinal ON bipolar cells, Go couples the metabotropic receptor mGluR6 to the TRPM1 channel and closes it in the dark, thus hyperpolarizing the cell. Light, via GTPase activating proteins, deactivates Go, opens TRPM1, and depolarizes the cell. Go comprises Gαo1, Gβ3 and Gγ13; all are necessary for efficient coupling. In addition, Gβ3 contributes to trafficking of certain cascade proteins and to maintaining the synaptic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
(87 reference statements)
0
11
0
Order By: Relevance
“…Interestingly, structural defects have already been shown in several cCSNB mouse models or in knockout mouse models lacking proteins involved in the mGluR6 signaling cascade. 35 40 However, the present report is the first to observe a structural defect specifically affecting cone, but not rod synapses. These results suggest that LRIT3 may participate in synaptogenesis reactions that are selective for wiring cones.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Interestingly, structural defects have already been shown in several cCSNB mouse models or in knockout mouse models lacking proteins involved in the mGluR6 signaling cascade. 35 40 However, the present report is the first to observe a structural defect specifically affecting cone, but not rod synapses. These results suggest that LRIT3 may participate in synaptogenesis reactions that are selective for wiring cones.…”
Section: Discussionmentioning
confidence: 44%
“…Proteins of the dystrophin–glycoprotein complex localized in the synaptic cleft of both rod and cone synapses, including dystroglycan and pikachurin, may be involved in the maintenance of a stable adhesion between rod spherules and rod ON-BC dendrites. 40 We evaluated the localization of pikachurin in the OPL of Lrit3 nob6/nob6 mice and showed that pikachurin normally localizes at the synaptic cleft of both rod and cone synapses, indicating that pikachurin is unlikely to be directly involved in the maintenance of the cone ribbon synapse. Similarly, it has been recently shown that a protein, ELFN1, is specifically expressed at the surface of rod spherules where it transsynaptically interacts with mGluR6, to enable formation of the rod synapse.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, deletion of the Gα o , Gβ3, or mGluR6 resulted in reduced accumulation of DCG at the synapse (Tummala et al 2016). These observations further support the idea of trans -synaptic coordination between the ON-BC signaling cascade and photoreceptors, and highlight that extracellular matrix may play an essential role in this process.…”
Section: Control Of Mglur6 Cascade Via Extracellular Interactions As mentioning
confidence: 99%
“…Recent findings suggest that the postsynaptic cascade of ON-BCs is further engaged in contacts with the photoreceptor presynaptic release apparatus ( Cao et al, 2015 ; Tummala et al, 2016 ; Wang et al, 2017 ). For example, the mGluR6 is directly recruited by the rod-specific molecule ELFN1 to the Ca V 1.4 channel complex, an interaction that is crucial for the physical assembly of rod synapses and the transmission of rod signals to rod ON-BCs ( Cao et al, 2015 ; Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%